The interacting physiology of COVID‐19 and the renin‐angiotensin‐aldosterone system: Key agents for treatment - Eugenie R. Lumbers; Richard Head; Gary R. Smith; Sarah J. Delforce; Bevyn Jarrott; Jennifer H.Martin; Kirsty G. Pringle (Wiley, 2022)
Abstract SARS‐CoV‐2 interacting with its receptor, angiotensin‐converting enzyme 2 (ACE2), turns the host response to viral infection into a dysregulated uncontrolled inflammatory response. This is because ACE2 limits the production of the peptide angiotensin II (Ang II) and SARS‐CoV‐2, through the destruction of ACE2, allows the uncontrolled production of Ang II. Recovery from trauma requires activation of both a tissue response to injury and activation of a whole‐body response to maintain tissue perfusion. Tissue and circulating renin‐angiotensin systems (RASs) play an essential role in the host response to infection and injury because of the actions of Ang II, mediated via its AT1 receptor. Both tissue and circulating arms of the renin angiotensin aldosterone system's (RAAS) response to injury need to be regulated. The effects of Ang II and the steroid hormone, aldosterone, on fluid and electrolyte homeostasis and on the circulation are controlled by elaborate feedback networks that respond to alterations in the composition and volume of fluids within the circulatory system. The role of Ang II in the tissue response to injury is however, controlled mainly by its metabolism and conversion to Ang‐(1‐7) by the enzyme ACE2. Ang‐(1‐7) has effects that are contrary to Ang II‐AT1R mediated effects. Thus, destruction of ACE2 by SARS‐CoV‐2 results in loss of control of the pro‐inflammatory actions of Ang II and tissue destruction. Therefore, it is the response of the host to SARS‐CoV‐2 that is responsible for the pathogenesis of COVID‐19.